Real‐world analysis of hospitalizations in patients with epilepsy and treated with perampanel. Issue 4 (13th August 2021) - Faught, Edward; Li, Xuan; Choi, Jiyoon; Malhotra, Manoj; Knoth, Russell L.
Abstract: Objectives: (1) To evaluate risk of hospitalization following initiation of perampanel (pre‐ and post‐analysis) and (2) to compare hospitalization rates following initiation of perampanel vs lacosamide. Methods: Patients were identified from Symphony Health's Patient Integrated Database if they had a prescription for perampanel (July 1, 2014‐June 30, 2016). Patients 4‐11 years of age with any partial‐onset seizure (POS) or ≥12 years of age with any POS or primary generalized tonic‐clonic seizure (GTCS) (pre‐post); or ≥12 years of age (perampanel vs lacosamide). The first fill of perampanel ("index date") marked the start of the analysis period. Patients had ≥1 additional fill for perampanel and ≥2 diagnoses for epilepsy or nonfebrile convulsion diagnosis during pre‐index (based on ICD‐9/ICD‐10 codes). Patients were matched using a 1:1 propensity scoring method for the perampanel vs lacosamide analysis. Primary outcome was hospitalization during the one year following medication initiation. Results: Pre‐ and post‐perampanel: N = 1771 (mean age 34 years, 55% female). One‐year all‐cause hospitalization risk ratio was 0.76 ( P < .05) and 36.2% with hospitalization during the pre‐period vs 29.5% in the follow‐up. One‐year epilepsy‐related inpatient hospitalization risk ratio was 0.72 ( P < .05) and 30.8% with hospitalization during the pre‐period vs 23.9% during follow‐up. In the perampanel and lacosamide cohorts, N = 1717 per cohort after matching, most baseline demographics were balanced. A higher percentage of subjects were prescribed ≥3 anti‐seizure medications for perampanel vs lacosamide (60.5% vs 57.7%, P < .001). The perampanel cohort had a 9.6% reduction in all‐cause hospitalizations vs 5.8% for the lacosamide cohort ( P < .05). Epilepsy‐related hospitalizations decreased from the pre‐index rate by 9.9% for perampanel and 8.3% for lacosamide ( P < .05). Among those with baseline hospitalizations, perampanel was associated with a 59.9% reduction in all‐cause hospitalizations vs 48.6% for lacosamide ( P < .05), and for epilepsy‐related hospitalizations, a reduction of 65.0% vs 58.9%, respectively ( P < .05). Significance: Perampanel was associated with a significant reduction in one‐year hospitalization risk.